PENGARUH PENERAPAN MANAJEMEN STRATEGI, TEKANAN PEMANGKU KEPENTINGAN YANG DIMEDIASI KAPABILITAS STRATEGIS TERHADAP KEBERLANGSUNGAN KINERJA ORGANISASI(STUDI PADA PERUSAHAAN PEMBANGKIT LISTIK DI INDONESIA) - Afrianda, Rio (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The incorporation of corporate programs focused on sustainability strategies contributes to the balance between economic growth and natural resource use. This issue is not limited to companies in developed markets but is also relevant for power generation companies that need to find ways to implement sustainable practices while improving organizational performance.In this context, the purpose of this study is to analyze whether strategic management can be considered a strategic capability that positively contributes to the performance of power generation companies in Indonesia. To achieve this objective, we conducted a quantitative study through a survey, collecting data from 162 companies. Based on univariate and multivariate analyses, the results indicate that strategic management can be considered a strategic capability for power generation companies in Indonesia, as strategic management has a significant relationship with organizational performance.